(untitled) (Journal for Studies in Humanities and Social Sciences, 2015)
This article analyses the language that the Shona speaking people in Zimbabwe use in naming death and dying, describing the dead, and consoling the bereaved. The research derives its linguistic analysis from a Shona socio-cultural-religious perspective. Related to this perspective, is the concept of saving face and easing the tension caused by death and this notion can be understood in the light of the politeness principle that guides human communication. Interviews and participatory observations were employed as data collection techniques in order to establish whether the Shona people use their language ordinarily or they fine-tune it to suit specific situations, particularly the unpalatable social situations like death and dying (language for specific purpose). Undergirded by these theoretical frameworks and methods, the study established that the Shona people have the tendency of creating, packaging and re-packaging their language use in relation to the social dilemma confronting them. Indirect ways of referring to tabooed matters such as death are in tandem with the Shona semantic philosophy in which by ‘indirection they find direction.’ In this regard, reference to death and dying often take the form of some blunt and euphemistic words or phrases, idiomatic and metaphorical expressions as a way of coping with death and dying. Euphemistic words and expressions allow the Shona people to talk about unpleasant notions and neutralise the unpleasantness, for example, the subjects of death and dying.